MODEL PERSEDIAAN PADA SUPPLY CHAIN DENGAN MEMPERTIMBANGKAN EMISI KARBON DAN PERMINTAAN YANG BERGANTUNG PADA HARGA JUAL PRODUK - Shabrina Chairunnisaa Novia Ramadhany; Wakhid Ahmad Jauhari; Cucuk Nur Rosyidi (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2023)
Emission from manufacturing contributes greatly to the increasing og greenhouse gas pollution. One of the activity in manufacturing is the supply chain. To deal with the risk of carbon emission, it is necessary to carry out green supply chain management, which is by implementing hybrid production, by regular production and green production. A company needs to consider the tradeoff between the use of green technology and the benefits that will be obtained. This research was conducted to form a supply chain inventory model by considering carbon policies and productselling price to maximize the joint total profit. The development of this model is carried by set the assumptions, formulating models, and gave the numerical examples by using secondary data. We used algorithm from the formulation model to find the optimal solution. The research is continued with a sensitivity analysis of the proposed scenarios by changing some of the parameter. This sensitivity analysis can be used as a consideration for a manager in making decisions according to those scenarios. The results of this study are the addition of green production facility is proven to reduce carbon emission by considering product selling price, lot size, number of shipping, and safety factor.